Case report of anti JMH: A high-titer, low-avidity antibody posing difficulty in immunohematological tests - Raghvan, Hari Priya; Yousuf, Rabeya; Thalith, Nor Fadzliana Abdullah; Loong, Tang Yee; Azma, RS Raja Zahratul (Indian Journal of Case Reports, 2024)
This report presents a patient with anti-John Milton Hagen (JMH) posing difficulties in the immunohematological test in the Blood Bank Unit of Universiti Kebangsaan Malaysia Medical Center. A 1-year-8-month-old boy was referred to our center to rule out acute leukemia from a private hospital. A crossmatch request was sent to the Blood Bank before the bone marrow biopsy. Our testing revealed his blood grouping as O Rh-D positive. His Direct Antiglobulin Test was positive, and his antibody screening and antibody identification showed weak pan-reactivity. However, reactions were negative with enzyme-treated cells. Red cell elution showed interestingly no reaction in the eluate, suspected to be due to drug-induced autoantibody. Further tests of antibody titration and neutralization test suggest it could be a high-titer low avidity (HTLA) antibody, most likely Anti-JMH. Although HTLA antibodies are clinically insignificant, they can cause confusion and delay in issuance of blood products. There are also cases of clinically significant HTLA antibodies. Determining the type of HTLA antibody may guide the extent of further testing required to utilize resources best and, most importantly, to assure patient safety.